Diagnostic value of combination of biomarkers for malignant pleural mesothelioma: a systematic review and meta-analysis - Zhu, Mucheng; Lu, Zhenhua; Guo, Hao; Gu, Xiaoting; Wei, Defang; Zhang, Zhengyi (Frontiers in Oncology, 2023)
Accurate diagnosis of malignant pleural mesothelioma (MPM) has always been a great challenge in the early stage. DNA and protein as biomarkers for the diagnosis of MPM have received a lot of attention, but the results are not very consistent. In this study, a systematic search using PubMed, EMBASE, Cochrane Library to identify relevant studies from the first day of databases to October 2021. We use the QUADAS-2 to evaluate the quality of eligible studies. We used the Stata 15.0 and Review Manager 5.4 software programs to perform the meta-analysis. In addition, bioinformatics analysis was performed at GEPIA to explore the relationship between related genes and survival time of MPM patients. We included 15 studies at the DNA level and 31studies at the protein level in this meta-analysis. All results showed that the diagnostic accuracy of the combination of MTAP + Fibulin-3 was the highest with the SEN 0.81 (95% CI: 0.67, 0.89) and the SPE 0.95 (95% CI: 0.90, 0.97), and bioinformatics analysis showed that the higher MTAP gene expression level was beneficial to improve the survival time of MPM patients. However, the conclusions may require further studies due to the limitations of the included samples.